Anthropologies of class power, practice and inequality - Carrier, James G.; Kalb, Don 1959-; Cambridge Books Online (Online service). (Cambridge Cambridge University Press, 2015)
Rising social, political and economic inequality in many countries, and rising protest against it, has seen the restoration of the concept of 'class' to a prominent place in contemporary anthropological debates. A timely intervention in these discussions, this book explores the concept of class and its importance for understanding the key sources of that inequality and of people's attempts to deal with it. Highly topical, it situates class within the context of the current economic crisis, integrating elements from today into the discussion of an earlier agenda. Using cases from North and South America, Western Europe and South Asia, it shows the - sometimes surprising - forms that class can take, as well as the various effects it has on people's lives and societies.
Introduction : class and the new anthropological holism / Don Kalb -- The concept of class / James G. Carrier -- Dispossession, disorganization and the anthropology of labor / August Carbonella and Sharryn Kasmir -- The organic intellectual and the production of class in Spain / Susana Narotzky -- Through a class darkly, but then face to face : praxis through the lens of class / Gavin Smith -- Walmart, American consumer-citizenship and the erasure of class / Jane Collins -- When space draws the line on class / Marc Morell -- Class trajectories and indigenism among agricultural workers in Kerala / Luisa Steur -- Making middle-class families in Calcutta / Henrike Donner -- Working-class politics in a Brazilian steel town / Massimiliano Mollona -- Export processing zones and global class formation / Patrick Neveling -- Global systemic crisis, class and its representations / Jonathan Friedman.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).
Keywords: Electronic books; Economic anthropology -- Case studies; Social classes -- Case studies; Social stratification -- Case studies; Social structure -- Case studies